pharmaceutical-sciences 2019
DOI: 10.36468/pharmaceutical-sciences.544
|View full text |Cite
|
Sign up to set email alerts
|

Drug Prescription Patterns in Osteoarthris Patients in a Tertiary Care Hospital in China

Abstract: Wang et al.: Drug Utilization Patterns for Osteoarthritis in a Chinese Province The study was conducted to evaluate the prescription patterns of various agents for osteoarthritis in a population specific cohort in Shandong Province, China. Data obtained from the Hospital Databases, which consisted of electronic medical records and prescription information. All the enrolled study subjects (n=212 546) are with a clinically detected osteoarthritis during 2010-2015. Medicine prescription pattern was demonstrated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Drug prescription pattern study in Chinese population was conducted and suggested that combinational drug therapy showed adverse effect and the patterns of drug therapy were noticed that 16% were on glucosamine, 12% was on chondroitin and 14% was on non-steroidal anti inflammatory drug. 36 Our findings indicated that, after one month treatment, Glucosamine sulphate with diclofenac sodium treated group and diclofenac sodium treated group showed much better results in terms of efficacy than other group which was celecoxib individual and in combination with glucosamine. Study demonstrated that both therapies show clinical improvement.…”
Section: Discussionmentioning
confidence: 51%
“…Drug prescription pattern study in Chinese population was conducted and suggested that combinational drug therapy showed adverse effect and the patterns of drug therapy were noticed that 16% were on glucosamine, 12% was on chondroitin and 14% was on non-steroidal anti inflammatory drug. 36 Our findings indicated that, after one month treatment, Glucosamine sulphate with diclofenac sodium treated group and diclofenac sodium treated group showed much better results in terms of efficacy than other group which was celecoxib individual and in combination with glucosamine. Study demonstrated that both therapies show clinical improvement.…”
Section: Discussionmentioning
confidence: 51%
“…We conducted a sensitivity analysis to explore heterogeneity related to risk of bias. When studies scored as having a high risk of bias were removed (n = 5 studies) (46–48,67,69), the pooled prescribing estimate remained similar (43.8% [95% CI 36.8, 51.1], n = 46 studies, high quality of evidence I 2 = 5.1%) (11,12,25,26,28–46,49–56,58–61,58–64,65,66,68,70–73) compared to the original estimate with high heterogeneity (43.1% [95% CI 36.3, 50.1], n = 51 studies, I 2 = 99.9%, low quality of evidence). A post hoc sensitivity analysis was conducted to explore the primary analyses using an alternative statistical approach (see Supplementary Figure 1, available on the Arthritis Care & Research website at https://doi.org/10.1002/acr.25157), which resulted in less conservative estimates than our original model.…”
Section: Resultsmentioning
confidence: 98%
“…The pooled prevalence of NSAIDs varied widely across geographical locations. The pooled estimate of NSAIDs prescribing was highest in South Asia at 83.4% (95% CI 74.8, 89.4; n = 4 studies, I 2 = 3.0%, moderate quality of evidence) (37,47,49,57), followed by Latin America and Caribbean at 68.5% (95% CI 66.8, 70.1; n = 1 study, I 2 = 0%, high quality of evidence) (33), East Asia and Pacific at 46.8% (95% CI 35.0, 58.9; n = 10 studies, I 2 = 31.7%, high quality of evidence) (12,25,32,38,40,51,53,58–60), Europe and Central Asia at 40.2% (95% CI 31.8, 49.3; n = 23 studies, I 2 = 12.2%, moderate quality of evidence) (26,27,28,29,39,42,43,45,46,48,50,52,54–56,61–68), Middle East and North Africa at 34.1% (95% CI 33.9, 34.3; n = 1 study, I 2 = 0%, high quality of evidence) (44), and North America at 32.6% (95% CI 16.9, 53.6; n = 12 studies, I 2 = 11.0%, moderate quality of evidence) (11,30,31,34–36,41,69–73). The stratified analyses results are summarized in Table 3 and the forest plot shown in Supplementary Figure 3, available on the Arthritis Care & Research website at https://doi.org/10.1002/acr.25157.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations